Design and experiment of the pneumatic double disc precision seed metering device for Chinese flowering cabbage - Yu, Yan; Ge, Ruchao; Li, Guoying; Zhang, Xing; Tan, Xiaozhi; Yi, Dazhi; Wang, Xiaomin; Xu, Zhuxin (International Journal of Agricultural and Biological Engineering, 2024)
Single seed metering devices for Chinese flowering cabbage planting machines have suffered such deficiencies as low efficiency, poor accuracy, and instability. To overcome these limitations, a pneumatic double disc precision seed metering device was designed. This innovative device can simultaneously plant four rows, considering the specific agricultural requirements and the geometric characteristics for Chinese flowering cabbage seeds. The precise parameters of the key component seed disc were derived through theoretical calculation. In addition, a detailed account was given for the working principle and workflow of the seed metering device. The discrete element method and EDEM software were employed to optimize the seed disc by exploring the effects of seed disc rotational speed and interleaving seed slots on seed viability. Orthogonal rotation experiments were conducted to evaluate the impact of seed disc rotational speed and negative pressure. While rates of qualified seeding, double seeding and missing seeding were adopted as test indicators. Testing results show that, at a seed disc rotational speed of 41.5 r/min and a negative pressure of 3.80 kPa, the average qualified seeding rate is 90.13%, the average missing seeding rate is 3.30%, and the average double seeding rate is 6.02%. These values satisfy the agricultural requirements for planting Chinese flowering cabbage. The findings can also provide valuable insights for the structural optimization and design of precision seed metering devices for Chinese flowering cabbage. Key words: Chinese flowering cabbage; precision seed metering device; double seed discs; pneumatic; experimentDOI: 10.25165/j.ijabe.20241704.8661Citation: Yu Y, Ge R C, Li G Y, Zhang X, Tan X Z, Yi D Z, et al. Design and experiment of the pneumatic double disc precision seed metering device for Chinese flowering cabbage. Int J Agric & Biol Eng, 2024; 17(4): 128–135.